Rare homozygous mutation in TUBB8 associated with oocyte maturation defect-2 in a consanguineous mating family - Qiong Xing; Ruyi Wang; Beili Chen; Lin Li; Hong Pan; Tengyan Li; Xu Ma; Yunxia Cao; Binbin Wang (BMC, 2020)
Abstract Purpose Variations in many genes may lead to the occurrence of oocyte maturation defects. To investigate the genetic basis of oocyte maturation defects, we performed clinical and genetic analysis of a pedigree. Methods The proband with oocyte maturation defect-2 receiving ovulation induction therapy and her parents were selected for clinical detection, whole exome sequencing and Sanger sequencing. One unrelated healthy woman received ovulation induction therapy as control. Mutations were assessed after frequency screening of public exome databases. Then homozygous variants shared by the proband and her parents were selected. Results Arrest of oocytes maturation was observed. A new missense mutation in TUBB8 (TUBB8: NM_177,987: exon 2: c. C161T: p. A54V) was identified, which was shown to be rare compared with public databases. The variant was highly conserved among primates, and was suggested to be deleterious by online software prediction. Conclusions The homozygote of this variant (TUBB8: NM_ 177,987: exon 2:c.C161T: p.A54V) might affect spindle assembly, cause arrest of oocyte maturation and lead to oocyte maturation defect-2.